2011
DOI: 10.1080/09645292.2010.545197
|View full text |Cite
|
Sign up to set email alerts
|

Equality of school choice: a study applied to the Spanish region of Aragón

Abstract: The aim of this paper is to test whether the distribution of students by social, cultural and racial characteristics is homogeneous between Spanish public (PS) and publiclysubsidised private schools (PSPS) or whether segregation exists between the profile of pupils attending each type of school. The theoretical framework is based on the contributions of researchers into school choice policies, while the empirical application uses a 2005 questionnaire answered by the final-year secondary school students of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 44 publications
4
6
0
3
Order By: Relevance
“…El uso de la base de datos de PISA hace que la mayoría de las investigaciones estimen la segregación para el conjunto del territorio estatal (Bonal, 2018;Ferrer, Ferrer & Castel, 2006Ferrer et al, 2011;Mancebón-Torrubia & Pérez-Ximénez, 2009Martínez y Ferrer, 2018;Murillo & Martínez-Garrido, 2018a, 2018bSicilia & Simancas, 2018). En algunos casos, cuando los datos lo permiten, se analizan también algunas o todas las Comunidades Autónomas (Bonal, 2018;Ferrer et al, 2011;Mancebón-Torrubia & Pérez-Ximénez, 2014;Martínez & Ferrer, 2018;Murillo & Martínez-Garrido, 2018a). Benito y González (2007), sin embargo, hacen una explotación especial de la base de datos de la Generalitat de Cataluña con lo que estiman la segregación en diferentes municipios.…”
Section: │2unclassified
See 1 more Smart Citation
“…El uso de la base de datos de PISA hace que la mayoría de las investigaciones estimen la segregación para el conjunto del territorio estatal (Bonal, 2018;Ferrer, Ferrer & Castel, 2006Ferrer et al, 2011;Mancebón-Torrubia & Pérez-Ximénez, 2009Martínez y Ferrer, 2018;Murillo & Martínez-Garrido, 2018a, 2018bSicilia & Simancas, 2018). En algunos casos, cuando los datos lo permiten, se analizan también algunas o todas las Comunidades Autónomas (Bonal, 2018;Ferrer et al, 2011;Mancebón-Torrubia & Pérez-Ximénez, 2014;Martínez & Ferrer, 2018;Murillo & Martínez-Garrido, 2018a). Benito y González (2007), sin embargo, hacen una explotación especial de la base de datos de la Generalitat de Cataluña con lo que estiman la segregación en diferentes municipios.…”
Section: │2unclassified
“…variables para operativizar el nivel socioeconómico de las familias de los estudiantes. Para los trabajos que hacen explotaciones especiales de PISA, que son la gran mayoría, utilizan como variable criterio el nivel socioeconómico y cultural (ESCS) que la propia base de datos proporciona, variable continua (Bonal, 2018;Ferrer, Ferrer & Castel, 2006;Ferrer et al, 2011;Mancebón-Torrubia & Pérez-Ximénez, 2010;Martínez & Ferrer, 2018;Murillo & Martínez-Garrido, 2018a, 2018bSicilia & Simancas, 2018). Mancebón-Torrubia y Pérez-Ximénez, (2010), además, usan las variables categóricas "tipo de trabajo de los padres" y "nivel de estudios de los padres".…”
Section: │3unclassified
“…In the Spanish public school system, most of the parent’s choice the school according with the standard of proximity to their homes. This criterion maintains the patterns of social stratification associated with residential zone ( Mancebon-Torrubia and Perez Ximenez-de-Embun, 2014 ). Social and economic neighborhood similarities are usually coincident with the social and economic structure of schools settled on the same neighborhood.…”
Section: Methodsmentioning
confidence: 86%
“…The availability of more schools increases the possibility of school choice and consequently generates competitive pressure from the market, which leads schools to seek better results (Becker, 1995;HOXBY, 2003). International literature on school choice indicates that it depends on factors such as: income, quality of school, safe, parental education and distance from the student's home to the educational institution (Burgess and Briggs, 2010;Chumacero et al, 2011;Dustan and Ngo, 2018;Hastings et al, 2006;HASTINGS and WEINSTEIN, 2007;Humble and Dixon, 2017;Koning and Van der Wiel, 2013;Mancebón-Torrubia and Ximénez-de-Embún, 2014;Nunes et al, 2015;Vega-Bayo and Mariel, 2015). In Brazil, Opice (2014), analyzing the choice of school in the state of São Paulo, found that the school quality is an important factor for the effect of student migration, being the best students who move.…”
Section: School Competitionmentioning
confidence: 99%